Power-lined : electricity, landscape, and the American mind - Wuebben, Daniel L. (University of Nebraska Press, 2019)
"In Power-Lined, Daniel L. Wuebben weaves together personal narrative, historical research, cultural analysis, and social science to provide a sweeping investigation of the varied influence of overhead wires on the American landscape and the American mind. Wuebben shows that overhead wires--from Morse's telegraph to our high-voltage grid--not only carry electricity between American places but also create electrified spaces that signify and complicate notions of technology, nature, progress, and, most recently, renewable energy infrastructure. Power-Lined exposes the subtle influences wrought by the wiring of the nation and shows that, even in this age of wireless devices, perceptions of overhead lines may be key in progressing toward a more sustainable energy future."--